HIV/AIDS Information Sources and Safe-Sex Practices among Artisans in Ilorin, Kwara State, Nigeria - Suleman, Abubakar Sidiq; Jimoh, Jide Peter (NIU Journal of Social Sciences; Vol 10 No 3 (2024): NIU Journal of Social Sciences, Vol. 10 No. 3, September 2024DO - 10.58709/niujss.v10i3.1989, 2024)
This study investigated HIV/AIDS information sources and safe-sex practices among artisans in Ilorin metropolis. Two research questions guided the study. Information Processing Theory was used to underpin the study. A descriptive research design was adopted for the study. The study found among others that, artisans have a high level of awareness about HIV/AIDS and safe sex. The study, therefore recommended among others, that, to achieve the vision 2030 (Goal 3, target 3.2) of the Sustainable Development Goal on ending HIV/AIDS as projected by WHO, the Federal and State Ministries of health and other stakeholders in HIV/AIDS containment should intensify health awareness campaigns’ efforts with special interest on HIV/AIDS containment and safe-sex practices through the use of appropriate information sources of the target audience. Keywords: Health communication, HIV/AIDS, Information sources, Safe-sex practices, Artisans